2002
DOI: 10.2307/1468440
|View full text |Cite
|
Sign up to set email alerts
|

Sampling effort affects multivariate comparisons of stream assemblages

Abstract: Multivariate analyses are used widely for determining patterns of assemblage structure, inferring species-environment relationships and assessing human impacts on ecosystems. The estimation of ecological patterns often depends on sampling effort, so the degree to which sampling effort affects the outcome of multivariate analyses is a concern. We examined the effect of sampling effort on site and group separation, which was measured using a mean similarity method. Two similarity measures, the Jaccard Coefficien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
90
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 88 publications
(92 citation statements)
references
References 55 publications
2
90
0
Order By: Relevance
“…However, at increased sample size, this dependence tends to disappear and attain a constant similarity value. Similar results were found by Wolda (1981) and Cao et al (1997Cao et al ( , 2002. This result shows the importance of determining adequate sampling efforts, because small sample sizes may underestimate similarities among samples of macroinvertebrate assemblages.…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations
“…However, at increased sample size, this dependence tends to disappear and attain a constant similarity value. Similar results were found by Wolda (1981) and Cao et al (1997Cao et al ( , 2002. This result shows the importance of determining adequate sampling efforts, because small sample sizes may underestimate similarities among samples of macroinvertebrate assemblages.…”
Section: Discussionsupporting
confidence: 84%
“…This results in high autosimilarity values and early curve stabilization. Similarly, Cao et al (2002) found that individual-based autosimilarity curves of stream macroinvertebrates stabilized earlier than sample-based ones, for both presence-absence and relative abundance data. However, in contrast to our results, they observed similar autosimilarity values for individual-and samplebased curves.…”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“…In contrast, precision can be expressed by comparing repeated measurements of the same quality. It is the basic idea in the development of the term sample representativeness (Cao et al 2002a(Cao et al , 2002b, a term used to describe how well a sample represents the community. In order to measure representativeness, two samples are collected from the same community and a measure of the similarity (or autosimilarity Cao et al 2003) determined.…”
Section: Introductionmentioning
confidence: 99%